Rapid disc diffusion antibiotic susceptibility testing for Pseudomonas aeruginosa, Acinetobacter baumannii and Enterococcus spp. (23rd November 2017) - Hombach, Michael; Jetter, Marion; Blöchliger, Nicolas; Kolesnik-Goldmann, Natalia; Keller, Peter M; Böttger, Erik C
Abstract: Background: We investigated the feasibility of rapid disc diffusion antibiotic susceptibility testing (rAST) with reading of inhibition zones after 6 and/or 8 h of incubation for Enterococcus faecalis, Enterococcus faecium, Pseudomonas aeruginosa and Acinetobacter baumannii . In addition, we evaluated discrimination of resistant populations from the WT populations at early timepoints and the requirement for clinical breakpoint adaptations for proper interpretation of rAST data. Methods: In total, 815 clinical strains [ E. faecalis ( n  =   135), E. faecium ( n  =   227), P. aeruginosa ( n  = 295) and A. baumannii ( n  =   158)] were included in this study. Disc diffusion plates were streaked, incubated and imaged using the WASPLab TM automation system. WT populations and non-WT populations were defined using epidemiological cut-offs. Results and conclusions: rAST at 6 and 8 h was possible for A. baumannii and enterococci with readability of inhibition zones >90%. Overall categorical agreement of rAST at 6 h with AST at 18 h was 97.2%, 97.4% and 95.3% for E. faecalis, E. faecium and A. baumannii, respectively. With few exceptions, major categorization error rates were <1% for A. baumannii, and vancomycin-resistant E. faecium were clearly separated from the WT at 6 h. For P. aeruginosa the average readability of inhibition zones was 68.9% at 8 h and we found an overall categorical agreement of 94.8%. Adaptations of clinical breakpoints and/or introduction of technical buffer zones, preferably based on aggregated population data from various epidemiological settings, are required for proper interpretation of rAST.